Catalases Promote Resistance of Oxidative Stress in Vibrio cholerae - Wang, Hui (Public Library of Science, 2012)

(untitled)
Oxidative stress is a major challenge faced by bacteria. Many bacteria control oxidative stress resistance pathways through the transcriptional regulator OxyR. The human pathogen Vibrio cholerae is a Gram-negative bacterium that is the causative agent of cholera. V. cholerae lives in both aquatic environments and human small intestines, two environments in which it encounters reactive oxygen species (ROS). To study how V. cholerae responds to oxidative stress, we constructed an in-frame oxyR deletion mutant. We found that this mutant was not only sensitive to H(2)O(2), but also displayed a growth defect when diluted in rich medium. Further study showed that two catalases, KatG and KatB, either when expressed in living cells, present in culture supernatants, or added as purified recombinant proteins, could rescue the oxyR growth defect. Furthermore, although it could colonize infant mouse intestines similar to that of wildtype, the oxyR mutant was defective in zebrafish intestinal colonization. Alternatively, co-infection with wildtype, but not katG-katB deletion mutants, greatly enhanced oxyR mutant colonization. Our study suggests that OxyR in V. cholerae is critical for antioxidant defense and that the organism is capable of scavenging environmental ROS to facilitate population growth.